From Organic to Precision Farming (Contemporary Publication) - Győrffy, Béla (Acta Agraria Debreceniensis, 2002)
The paper presents a short review of the different types of farming systems: Biofarming, Organic farming, Alternatíve farming, Biodynamic farming, Low input sustainable agriculture (LISA) Mid-tech farming, Sustainable agriculture, Soil conservation farming, No till farming, Environmentally sound, Environmentally friendly, Diversity farming Crop production system, Integrated pest management (IPM), Integrated farming, High-tech farming Site specific production (SSP), Site specific technology (SST), Spatial variable technology, Satellite farming. Precision farming It concludes that the various systems are applicable in different ratios and combinations depending on the natural and economic conditions. The author predicts an increase in precision technologies , the first step being the construction of yield maps compared with soil maps and their agronomic analysis. Based on this information, it will be necessary to elaborate the variable technology within the field, especially for plant density, fertilization and weed control. The changes in weed flora during the past fifty years based on 10.000 samples within the same fields using the weed cover method are presented.